A Study on ICT in Fatwa Management in Malaysia - Mohd Alwi, N. H.; Azania, N. (Universiti Sains Islam Malaysia, 2024)
This paper reports a study of the usage of information communication and technology (ICT) in fatwa management at Mufti departments in Malaysia. For this research ICT is the term used to explain the usage of technology such as computer to manipulate data for the purpose of disseminations and communications. The usage of ICT was studied based on four basic operations that are input, process, output and storage. This research also identifies the factors that limit the ICT usage in fatwa management. The data were collected through interviews and survey at Mufti departments in Malaysia. The outcome of this research shows that generally ICT is being used in fatwa management at Mufti departments in Malaysia and specifically the ICT is more applied for storage purposes. Nevertheless the technologies and infrastructures available are limited. This research also reveals that the usage of ICT does help in managing fatwa efficiently and effectively for the beneflt of the Muslim community.